1998
DOI: 10.1038/sj.jhh.1000558
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic status and blood pressure: an overview analysis

Abstract: Background: Mortality rates from hypertension relatedThe finding of an SES gradient in BP, despite adjusting for treatment in some studies and the lack of consistent diseases such as coronary heart disease, hypertensive heart disease, stroke and end stage renal disease show SES differences in hypertension treatment rates, makes differential treatment an unlikely explanation for the SES an inverse association with socio-economic status (SES). gradient in BP. A substantial part of the SES gradient was accounted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
272
6
10

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 348 publications
(312 citation statements)
references
References 31 publications
(57 reference statements)
24
272
6
10
Order By: Relevance
“…7 In summary, our findings showed that hypertension in rural Vietnam is becoming a serious problem, which should no longer be ignored, both because of its magnitude and the unacceptably high unawareness rate in the population.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…7 In summary, our findings showed that hypertension in rural Vietnam is becoming a serious problem, which should no longer be ignored, both because of its magnitude and the unacceptably high unawareness rate in the population.…”
Section: Discussionmentioning
confidence: 70%
“…This inverse association was also found in almost all studies carried out in developed countries such as the United States of America, Canada, Australia, Sweden and the Netherlands. 7 In developing countries, the pattern of association varied: meanwhile, hypertension was found to be inversely associated with educational levels in some studies, for example, in Brazil 39 and China, 40 while a direct association was observed in others, for example in India. 41,42 Mortality from cardiovascular disease in Bavi in 2000 was also higher among less educated people but the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However most of this effect can be explained by an increased proportion of obese subjects and higher alcohol intake in the most deprived socioeconomic groups. 16 Similar relationships exist for educational status. 17 Environmental influences early in life may affect blood pressure as an adult and into old age.…”
mentioning
confidence: 84%
“…Special efforts to improve eating patterns of less educated strata can contribute importantly to overIntroduction An inverse relationship between education and blood pressure (BP) of individuals has been found repeatedly in cross-sectional surveys of US population samples of varied ethnicities and in many other population samples, particularly from economically developed countries. [1][2][3][4][5][6][7][8][9][10][11][12][13] Correspondingly, the CAR-DIA and Western Electric prospective studies found that people with less educational attainment at baseline experienced greater BP increase over the ensuing years. 14,15 Little information is available on factors accounting for these findings.…”
mentioning
confidence: 99%